FISH using a gag-like fragment probe reveals a common Ty3-gypsy-like retrotransposon in genome of Coffea species - Yuyama, Priscila Mary; Protasio Pereira, Luiz Filipe; dos Santos, Tiago Benedito; Sera, Tumoru; Vilas-Boas, Laurival Antonio; Lopes, Fabricio Ramon [UNESP]; Aparecida Carareto, Claudia Marcia [UNESP]; Laforga Vanzela, Andre Luis (Canadian Science Publishing, Nrc Research Press, 2012)
The genus Coffea possesses about 100 species, and the most economically important are Coffea canephora and Coffea arabica. The latter is predominantly self-compatible with 2n = 4x = 44, while the others of the genus are diploid with 2n = 2x = 22 and mostly self-incompatible. Studies using molecular markers have been useful to detect differences between genomes in Coffea; however, molecular and cytogenetic studies have produced only limited information on the karyotypes organization. We used DOP-PCR to isolate repetitive elements from genome of Coffea arabica var. typica. The pCa06 clone, containing a fragment of 775 bp length, was characterized by sequencing and used as a probe in chromosomes of C. arabica and six other species: C. canephora, Coffea eugenioides, Coffea kapakata, Coffea liberica var. dewevrei, Coffea racemosa, and Coffea stenophylla. This insert shows similarities with a gag protein of the Ty3-gypsy-like super-family. Dot blot and FISH analyses demonstrated that pCa06 is differentially accumulated between species and chromosomes. Signals appeared scattered and clustered on the chromosomes and were also associated with heterochromatic regions. While the literature shows that there is a high karyotype similarity between Coffea species, our results point out differences in the accumulation and dispersion of this Ty3-gypsy-like retrotransposon during karyotype differentiation of Coffea.
Keywords: Coffea; dot blot; Fish; gag sequence; Retrotransposon; Ty3-gypsy-like